PEMANFAATAN SUKUN SEBAGAI BAHAN ALTERNATIF PEMBUATAN MAYONAISE NABATI DENGAN PENAMBAHAN RPO (MINYAK SAWIT MERAH) SEBAGAI SUMBER BETA KAROTEN - Nur Wahyuni; Titik Sulistyani (Jurnal Socia Akademika, 2021)
Breadfruit mayonnaise is a semi-solid emulsion with the addition of red palm oil (RPO) and salad oil. Breadfruit is a functional food with high nutritional content so that it has the potential to be used as an alternative food. There is a high carotenoid content in red palm oil as a source of provitamin A. This type of research is an experiment of RPO and salad oil to make breadfruit mayonnaise with four comparative variations, namely X1 samples (5gr:45gr); X2 (10gr:40gr); X3 (15r:35gr); and X4 (25gr:25gr). The mayonnaise gratitude test conducted on 30 Yogyakarta Academy of Social Welfare "AKK" was with a favorite test (hedonic) and analyzed with the ANOVA test. The nutritional content analyzed is betacarotene using a spectrophotometer performed in the Lab. Chem-Mix Pratama Yogyakarta. Results from the hedonic test of mayonnaise characteristics obtained the highest score on x3 mayonnaise samples (15r:35gr) (color: 3.33; aroma: 3.03; texture: 3.00; and flavor: 3.33). Based on the ANOVA test, obtained Sig value. (color 0.000; aroma 0.001; texture 0.005; and flavor 0.000) which means there is a noticeable difference in the characteristics of mayonnaise. X3 sample breadfruit mayonnaise (15r:35gr) produces orange mayonnaise characteristics, with no aroma, dense texture, breadfruit flavor, betacarotene content 8181.0935ug./100g. It was concluded that a sample of mayonnaise with RPO 15gr and 35gr salad oil is preferred and contains betacarotene, which can provide vitamin A intake. Mayonnaise is also good for vegetarians. It is recommended that this mayonnaise be used as a food source to prevent vitamin A deficiency.